Isatin Aldazines Synthesis using A Proton Exchanged Algerian Montmorillonite Clay as Acid Eco-friendly Catalyst - Boumadiene Benlahreche; Assya Taleb; Mokhtar B. Lahrech; Salih Hacini (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
An efficient and easy procedure is developed for the synthesis of isatin aldazines or bis-Schiff bases of isatin, catalyzed by a proton exchanged Algerian montmorillonite clay (MMT-H+) as green catalyst. The products were obtained in two catalyzed steps under conventional heating in ethanol. Isatin-3-hydrazone obtained from the reaction of isatin with hydrazine monohydrate reacts in the second step with the appropriate aromatic aldehydes to give the desired products in good yields. The main advantages of using this protonated solid non-toxic catalyst in this synthesis are its availability and low cost, the simplicity of its use, the recycling possibilities without significant loss of its catalytic activity and its environmentally benign process.